Evaluation of Container Terminal Arrangement By Computer Simulation - Takeshi Shinoda; Hideyo Inutsuka; Putu Hangga; Tiago Novaes Mathias (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
With growing ship size and demand for effective handling of container cargoes in recent years, automation has inevitably took place in almost all aspect of modern terminal operation. So far, automation has been led by the large terminals in Europe and North America and soon it will become a pressure for terminals in developing countries to go for automation. The drawbacks heavily rely on the initial investment cost and question arises with regard to effectiveness of automation for medium and small size container terminals. A visual environment that simulates container terminal operation is developed to facilitate investigation advantage and disadvantages of automated container terminal compared to conventional container terminal. A discrete event model for container handling process and agent-based model for path mover flow system is built and validated based on operating terminal in real world and visually simulated to serve the objective. The result of the computer simulation is an evaluation of performance metric for both terminal concepts under similar arrangements. In addition, visual simulation was able to notify the area where advantage and disadvantage of both concepts will take place during operation.